Income polarization and stagnation in a stochastic model of growth: When the demand side matters - Thomas Gries (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This contribution is motivated by two stylized observations, the slowdown in growth, and a simultaneous income polarization in many advanced economies. While mainstream neoclassical and endogenous growth theory cannot sufficiently explain the nexus, we argue that the demand side plays a role. We suggest a hybrid model that is based on a standard product-variety model with intermediate goods, and which is frequently used in endogenous growth theory. Even if there are stochastic frictions, prices are generally flexible. As we want to look at polarization effects, we model two income groups, labor and financial wealth owners. Further, we obtain a sustainable steady-state equilibrium by suggesting an unconventional equilibrium concept in a stochastic environment. We define equilibrium as a stationary no-expectation-error equilibrium. This equilibrium concept relates to the Nash idea of individual stationary behavior as long as all expected values are the effectively realized values. Even if potential growth is generated only by the supply side, endogenous effective demand restricts level and growth rate of the income path. The growth rate is semi-endogenous and determined by entrepreneurs' success of market entry of new technologies. Our hybrid model bridges a gap between Keynesian and neoclassical (and endogenous) ideas of economic growth.
Keywords: D33; O40; E10; 330; product-variety model; demand-constrained growth; semi-endogenous growth